UNPACKING THE RESISTANCE OF TRADITIONAL MARKET TO DIGITAL PAYMENT: A QUALITATIVE APPROACH - Oktaviani, Retno Fuji (Riset: Jurnal Aplikasi Ekonomi Akuntansi dan Bisnis, 2024)
This research aims to discover how knowledgeable traditional market traders are regarding digital payment technology, what challenges traders face when trying or considering using digital payments, and how prepared traders are for traditional market digitalization programs. The research method used is qualitative research, which is conducted in-depth interviews with traditional market traders at Kebayoran Lama Market, South Jakarta. The research was conducted in June 2024 and visualized using NVIVO software. The interview results show that traditional market traders' understanding of digital payments shows that awareness, education, trust, and security factors play an essential role in adopting this technology. Overcoming the challenges of adopting digital payments requires a holistic approach that includes improving security and privacy, user education and training, developing technological infrastructure, reducing transaction costs, encouraging social and cultural influence, and increasing merchant support. Meanwhile, to increase the readiness of traditional market traders in facing digitalization, several strategic steps are needed, including comprehensive education and training to increase optimism and reduce discomfort, providing easily accessible technical support, security campaigns to explain digital payment system security measures, as well as promotions and incentives to encourage technology adoption.